The Urgency of Establishing an MPR Honorary Court in Strengthening Legislative Ethics in Indonesia - Nia Laila Apriliani; Jefik Zulfikar Hafizd; Am’mar Abdullah Arfan; Mohamad Rana; Saiful Ansori; Rohana Rohana (Journal of Law Justice (JLJ), 2026)
The purpose of this research is to examine juridically the urgency of establishing the Honorary Court of the People’s Consultative Assembly (Majelis Permusyawaratan Rakyat / MPR) as an ethical supervisory body in order to strengthen a clean, accountable, and integrity-based constitutional system. The method applied is a normative juridical approach through analysis of laws and regulations, relevant legal decisions, and ethical principles as stated in MPR Decree Number VI/MPR/2001. The novelty of this study lies in its focus on the MPR, which unlike the House of Representatives (DPR) with its Honorary Council, has not yet institutionalized an ethical body, thus leaving a legal and institutional gap that requires urgent attention. The findings of this study show that the establishment of the MPR Honorary Court is a crucial need to create an ethical supervision system that is both preventive and repressive toward its members, thereby enhancing institutional accountability. In conclusion, the existence of such an institution is expected to strengthen the legitimacy and public trust in the MPR’s representative function, with the main recommendation being the drafting of internal regulations that define the structure, authority, and working mechanisms of the Honorary Court as an integral part of legislative institutional reform.